BAHASA SUNDA PERBATASAN (BORDERLAND) DI KECAMATAN DAYEUHLUHUR, KABUPATEN CCILACAP, JAWA TENGAH: PRIMORDIALISME MASYARAKAT PERBATASAN JAWA TENGAH DAN JAWA BARAT - Nani Darheni (Fakultas Seni Rupa dan Desain ITB, 2010)
Border, connecting the two geographical areas in some parts of Indonesia warned that until now inviting and contains potential conflicts, even conflicts between nations. Border (Borderland 'unique community') may also be attached to the District Dayeuhluhur, area located in Central Java province and borders with West Java Province. Although located in Central Java Province, the local language used by the community is not the Java language, but Sundanese language that is different from Sundanese lulugu 'standard' in Bandung. ` Geographically Dayeuhluhur consists of mountainous areas and urban areas. Dayeuhluhur has the potential of a culture that made the nation's cultural treasures should be preserved. The potential of language as a vehicle or medium interact socially in daily communication. The majority of the population of this region using the language of instruction language. The de facto Dayeuhluhur located in Central Java province, but in terms of language use of Sundanese, Javanese language instead. This makes the plurality or diversity of languages as an integral tool of effective. This study aims to describe the Sundanese border in the District of Dayeuhluhur based on the results of field research. Research method used for descriptive comparative look at the technique, record, direct interviews with native speakers and literature study. Borderland (language border) in this region include aspects of phonological, lexicon (at most), morphological, and syntactic. Now, in District Dayeuhluhur, Cilacap, there is the use of Javanese and Sundanese (in addition to Indonesian language) which has distinctive characteristics compared to other languages. Keywords: Border Sundanese, Borderland, morphosyntax, Primodialism.